2003
DOI: 10.1046/j.1365-8711.2003.06755.x
|View full text |Cite
|
Sign up to set email alerts
|

V838 Mon: an L supergiant?

Abstract: We present a 0.8–2.5 μm spectrum of the peculiar variable V838 Mon, obtained on 2002 October 29. We see one of the coolest stars – certainly the coolest supergiant – ever observed, with deep water bands and other spectral signatures normally associated with very late L and T brown dwarfs. We suggest that V838 Mon may be the first known ‘L supergiant’.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 19 publications
6
84
1
Order By: Relevance
“…Finally, association of the OH with the outer photosphere enables the mass of the outer photosphere to be estimated, resulting in 0.008-0.03 M (it depends on the assumed area of the outer photosphere, 1 2A p ). This is in agreement with the estimates made by Evans et al (2003).…”
Section: Derived Quantitiessupporting
confidence: 94%
See 1 more Smart Citation
“…Finally, association of the OH with the outer photosphere enables the mass of the outer photosphere to be estimated, resulting in 0.008-0.03 M (it depends on the assumed area of the outer photosphere, 1 2A p ). This is in agreement with the estimates made by Evans et al (2003).…”
Section: Derived Quantitiessupporting
confidence: 94%
“…A few months after the outburst, V838 Mon was found to be part of a binary system, with the companion being a B3 V star (Desidera & Munari 2002;. Infrared observations interspersed with our own and covering the 1-2.5 m region have been reported by Evans et al (2003), who speculate that V838 Mon may be an L giant, an interesting possibility in view of the object's low temperature and pressure.…”
Section: Introductionmentioning
confidence: 60%
“…colonel Roche, BP 44346, 31028 Toulouse, France spectral types F, G, and K, to a very cool M-giant (Evans et al 2003). Loebman et al (2015) found the star to show features of mixed spectral type, from M3 dwarf to mid-L supergiant: the atmosphere is obviously not a conformist.…”
Section: Post Outburst V838 Mon Varied Throughmentioning
confidence: 99%
“…The eruption of V838 Mon in Feb. 2002(Munari et al 2002 reached an apparent magnitude of V = 6.7 mag and was studied quite closely. The light curve showed three maxima and a consistent change of colours redwards as the spectrum reached an L supergiant phase at the end of the year (Evans et al 2003). The resulting circumstellar light echo was used to obtain a distance estimate of 6.1 ± 0.6 kpc, corresponding to a peak absolute magnitude M V = −9.8 (Bond et al 2003;Sparks et al 2008).…”
Section: Introductionmentioning
confidence: 99%